Why do we need 'Problem-oriented Innovation System (PIS)' for solving macro-level societal problems? - Ghazinoory, Sepehr; Nasri, Shohreh; Ameri, Fatemeh; Montazer, Gholam Ali; Shayan, Ali (Technological Forecasting and Social Change, 2020)
The number of theories of innovation systems has grown considerably over the past two decades and several innovation system approaches have been developed. The focus of most has been on the development of technological innovations which create economic value. However, addressing macro-level societal problems – sociotechnical and environmental challengesin which the production, dissemination and use of social and technical knowledge and technology can potentially resolve the problem – has been overlooked. The present study argues that in order to resolve such problems, a combination of technical innovations (covering the technological aspects of the problem) and social innovations (covering the social aspects of the problem) are required.Instead of focusing on the development of a particular technology or industry, an innovation system must focus on solving problems; it must utilize technical innovations alongside economic and social innovations to do so. To this end, the present study highlights the need for a framework for the analysis of macro-level societal problems by reviewing innovation systems literature and proposes a new approach named "Problem-oriented innovation systems". We conceptualize this approach based on event history analysis and through case study of the US air pollution problem and the way it was successfully resolved by using technical and social innovations.The results show that a problem-oriented innovation system has eight functions: System monitoring and guidance, technical and social knowledge creation, technical and social entrepreneurship, knowledge dissemination, collaboration and synergy, public awareness, standardization and resource mobilization. Finally, a framework for analyzing the innovation process is proposed to solve the macro-level societal problem. This approach can be used to solve global problems such as global warming and climate change which ask for collaboration among different countries.
Keywords: Changement systémique; Durabilité; Réservé UdeM; Système d'innovation